Test the Effectiveness Volume of Hydroton Media on Mustard Plant (Brassica chinensis Var. Parachinensis) Using Auto Kapiler - Septia, Erfan Dani; Maftuchah; Nurfutika, Mifta (Universitas Muhammadiyah Malang, 2022)
This study aims to determine the level of effectiveness the hydroton growing media on mustard plants using the Auto Kapiler hydroponic method with 3 treatments; M1 with hydroton growing media of 2,54 liters (volume 50%), M2 with hydroton growing media of 3,78 liters (75% volume), and M3 with hydroton growing media of 5,04 liters (100% volume). The research was conducted on Jl. Tirtonadi RT. 25 / RW. 04, Jatikerto village, Kromengan sub-district, Malang district which will take place from April 25 to June 14, 2022. Some of the materials and tools used during the research are; hydroton growing media, auto capillary, AB-Mix nutrition, pH meter, and EC meter. Variable observations made consist of; plant height (cm), number of leaves (strands), leaf width (cm), root length (cm), and plant fresh weight (grams). Data analysis in this study used a simple Completely Randomized Design (CRD) with 4 replications and 3 treatments. The data obtained were further analyzed using the least significant Least Significant Different (LSD) α 5% level which was then further analyzed using a linear regression. The results showed that the M3 treatment (100% hydroton growing media volume was 5,04 liters) was better than the M2 treatment (75% hydroton growing media volume 3,78 liters) and M1 (50% hydroton growing media volume 2,52 liter).